ZAKAT BATU AKIK HASIL TAMBANG MENURUT PERSPEKTIF HUKUM ISLAM (Studi Kasus di Kecamatan Beutong Kabupaten Nagan Raya) - RIZKIYALLAH, RIZKIYALLAH (Petita : Jurnal Kajian Ilmu Hukum dan Syariah, 2016)
In fiqh (Islamic jurisprudence), some wealth has been imposed zakat such as agriculture, mining, and livestock. In particular, today’s society has also paid zakat on agate mines as practiced by the community in Beutong Sub-district, Nagan Raya District. It is thus interesting to examine more on the agate zakat from the perspective of the Islamic law. The questions posed in this study were whether agate mines shall be imposed zakat according to the Islamic law, how the public perception of the zakat was, and how the zakat payment system of agate and the nisab (the amount of wealth liable for zakat) levels were in the Beutong community. The public perceived that agate could be a useful economic resource, and therefore, the zakat on agate has become compulsory provided that it has come to its nisab. Beutong’s community has followed the rule of zakat by paying the zakat of agate trading. The trade of agate has been subject to zakat when it has reached its nisab of 2.5% and the haul (a full year). .